Análise das taxas de internações hospitalares por fratura de fêmur em idosos no estado do Rio Grande do Sul - Del Castillo, Bruna Lencina (2017)
INTRODUCTION: The growth of the elderly population is a phenomenon that has been occurring all the world and has deserved prominence in recent years. Aging brings many of structural and functional changes that compromise the motor performance skills, contributing significantly to the increased risk of falls in this population. One of the consequences of falls in the elderly is the fractures, especially the femur fracture, which causes a great impact on the functional capacity of the elder people due to autonomy and independence lost and the consequent reduction in the quality of life of these individuals. Thus, this study aims to know the context of hip fracture in the oldest countries in the world through a review, as well as to analyze hospitalizations for femoral fracture in Rio Grande do Sul State. METHODOLOGY: The present study is a descriptive and ecological study with an analysis of the behavior of hospital admissions for femoral fracture in the elderly in the state of Rio Grande do Sul, in which data from hospital admission in the state of Rio Grande do Sul were used for fracture of femur, from the Hospital Information System of the Unified Health System (SIH / SUS). RESULTS: As a result of the present study, it was possible to observe an increase in the general rates of hospitalization for femoral fracture from 2005 to 2012 in the State of Rio Grande do Sul, but with a decline in those rates when the 60-year or more. However, when analyzing the time cut from 2010 to 2012, it was possible to observe an increase in hospitalization rates for femur fractures in the elderly and regional disparities in relation to the Regional Health Coordination. CONCLUSION: Despite the aging of the world population, the hospitalization rates of femoral fractures has been showing different trends in analyzed countries (Japan, Italy, Finland and Germany), indicating that only the increase in the elderly population is not a major factor for the increase of femoral fractures. In Rio Grande do Sul State, regional differences are also observed, emphasizing the need of situational and regionalization analysis for a more effective health system. The analysis of the behavior of the hospitalization rates for femur fracture evidenced a reduction of the rates when comparing 2005 to 2012, but with an increase of the same ones in the last years of analysis (2010-2012). The observed regional and temporal differences evidenced the need for periodic analyzes to evaluate the effectiveness of the actions implemented by the health system in order to reduce the number of occurrences and to encourage the formulation of new strategies to deal with this problem in each region its reality.